Prime Savings with Prizes in an Islamic Perspective - Muhammad Wandisyah R Hutagalung; Andri Soemitra; Arbanur Rasyid; Fitri Yani Lubis; Ismail Nura (Islamic Banking : Jurnal Pemikiran dan Pengembangan Perbankan Syariah, 2021)
Prime Savings with Prizes is a savings that uses a mudharabah agreement. The problem in this research was that after the customer opens an account of prime savings with prizes, the customer will get a prize, even though the customer has not managed the savings by the bank. The provisions in syari'ah financial institutions, that the prize is a prize at the end of the period. This study aimed to determine how the implementation of Prime Savings at PT. Bank Muamalat, Padangsidimpuan branch office and to find out the concept of prime savings with prizes seen from an Islamic perspective. DSN Fatwa No.02/DSN-MUI/IV/2000 concerning savings, that the profit sharing must be stated in the form of a ratio and in the account opening contract. Second, DSN Fatwa No.86/DSN-MUI/XII/2012 concerning prizes in raising funds for syari'ah financial institutions. The research method used was a qualitative method with a descriptive approach. The types of data used were primary data sources and secondary data sources. Data processing techniques. The technique of collecting data were interviews, observation and documentation. Data analysis techniques were data reduction, data editing, data presentation, data conclusion and verification, and data validity techniques. This study found that the concept of giving gifts is a gift given by muamalat bank which is a gift at the beginning of the period, and the concept of gifts is based on interviews from ulama’ and lecturers when viewed from an Islamic perspective that gifts are a voluntary gift from someone to another without expecting a reward so that it is allowed in muamalah without being wronged.